Supporting Ph.D. students' skills development: A three-stage doctoral program - Chaló, Paulo; Huet, Isabel; Nikoletou, Dimitra; Pereira, Anabela (Frontiers in Education, 2023)
Introduction Sustainable development is increasingly recognized as a crucial component of education at all levels, including specialized academic work. As a result, the importance of Ph.D. training in producing highly skilled academics and professionals who can contribute to sustainable development has been acknowledged, leading to increased investments in doctoral training across Europe. However, the diversity in Ph.D. training across countries and universities suggests a lack of studies based on best practices for developing effective doctoral training programs. Methods This study aimed to contribute to this discussion by combining the perspectives of 31 Ph.D. supervisors and directors from Portugal and England regarding the best practices for Ph.D. training. Participants from different disciplines were interviewed using semi-structured face-to-face interviews, and the data were analyzed using inductive thematic analysis. Results The study found that, despite coming from different countries, the participants' perceptions regarding the challenges and strategies for improving doctoral education were similar. Based on these findings, the study proposes a three-stage program for structuring doctoral training, consisting of initial intensive training, assessment of individual needs, and tailored training. Discussion The proposed program has the potential to be valuable in the development or restructuring of Ph.D. programs to address the primary needs of Ph.D. students, optimize institutional resources, and promote on-time completion by facilitating the timely development of necessary competencies for Ph.D. research. Furthermore, this approach could enhance the quality of Ph.D. education, broaden the spectrum and quality of graduates' competencies, and contribute to achieving sustainable development goals.